The Dangerous Life of a Storm Chaser: A Lightning Strike Injury Causing Serious Injury - Jeffrey Shipman DO; Brittany Carver DO; Kelly Painter MD; Stacia Shipman DO (SAGE Publishing, 2020)
Lightning strikes to people are rare events that cause significant injuries and mortality when they do occur. We describe an uncommon case of a storm chaser in Oklahoma who was struck by lightning who suffered cutaneous burns, bilateral tympanic membrane ruptures, as well as pulmonary edema, which is an atypical finding in survivors. This case report highlights several injury patterns seen in lightning strike cases and provides evidence that these patients should be managed at a center with multidisciplinary services available.